Study of fouling control strategy for high flux output using nanofiber membrane in MBR - Tan, Si Hua (2017)
Membrane Bio-Reactor (MBR) is a growing technology which requires constant innovations. The nanofiber membrane is a new generation of membranes. It is still a relatively new concept to incorporate this membrane in the MBR. Hence, its potential in this aspect remains questionable. This study is established to provide answer to its applicability. This study has successfully established a closed looping MBR system using nanofiber membrane for the filtration process to treat synthetic wastewater. The system has run for 152 days; the system was running at the optimized configuration for 30 days. During the whole project duration, permeate flux was quantified to evaluate the membrane fouling. There are the three types of observable fouling the MBR has encountered in this study. Additionally, it was found that the incorporation of mechanical washing, chemical washing, operating cycle and pressure release as fouling control strategy has permitted the stable flux of the system to maintain at an average stable flux of 33 LMH.